Dielectric and microwave absorption properties of Na0.5Bi0.5TiO3–SrTiO3 system. Issue 1 (26th October 2021) - Dutta, Alo; Gorai, Anupam; Mandal, Dipika; Mandal, Kalyan
Abstract: In this work, we have investigated the structural, dielectric and microwave properties of Sr x (Na0.5 Bi0.5 )1– x TiO3 (0.25 ≤ x ≤ 0.75) prepared using the solid state reaction technique. The Rietveld refinement of the X-ray diffraction pattern at room temperature of the samples is performed to confirm the phase formation as well as the crystal structure of the materials. All the materials are synthesized in cubic Pm3m phase. The low-frequency dielectric properties of the materials are investigated using alternate current impedance spectroscopy in the frequency range from 50 to 1 MHz. The temperature dependence of the dielectric constant at different frequencies gives diffuse peaks which have been attributed to the occurrence of relaxor behavior in these materials. The magnitudes of ε ′m, the maximum value of dielectric constant and T m, the temperature corresponding to ε ′m are decreased with an increase of Sr 2+ ion in the materials. The Vogel-Fulcher relation has been considered to explain the relaxor behavior of the materials. The microwave dielectric properties as well as reflection loss of the materials have also been studied in the frequency range from 1 GHz to 15 GHz.